Job Analysis Implementation in Employee Placement at the Muara Kelingi District Office, Musi Rawas Regency: Implementasi Analisis Jabatan dalam Penempatan Pegawai di Kantor Camat Muara Kelingi, Kabupaten Musi Rawas - Abdul Rota; Alexsander; Henny Aprianty (JURNAL ISIP VOICE : Jurnal Ilmu Sosial dan Ilmu Politik, 2026)
This study evaluates the implementation of job analysis, specifically focusing on job specifications for employee placement at the Muara Kelingi District Office, Musi Rawas Regency. Within the public sector, aligning human capital with specific organizational demands is critical for service excellence. However, indications of a mismatch between employee competencies and job requirements remain prevalent. Employing a qualitative descriptive approach, data were gathered through in-depth interviews, participant observation, and document analysis. Informants, comprising district leaders and staff, were selected via purposive sampling. The data analysis utilized an interactive model encompassing data condensation, display, and verification. Findings reveal that job specifications are not optimally utilized as the primary parameter for placement. In the knowledge dimension, employees rely heavily on normative regulations rather than developing innovative problem-solving frameworks. Within the skills dimension, severe mismatches exist, such as the assignment of non-accounting personnel to financial subdivisions, alongside pervasive deficiencies in technical and digital competencies. Furthermore, the ability dimension exhibits gaps in managerial capability, particularly evident in supervisory roles, lacking alignment with their educational background. The study concludes that the merit system principles envisioned by current bureaucratic reform policies are compromised. Strategic restructuring of personnel based on rigorous job analysis and systematic competency development is urgently recommended.